Dampak Penyalahgunaan Aplikasi Dana Dalam Transaksi Judi Online di Kalangan Remaja - Rinduni, Ridha; Ramadani, Anggun Tri; Arrizal, Brian Hafiz (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Indonesia's positive economic growth, reaching around 5% per year, has driven the development of the digital sector, including the use of e-wallets, especially among teenagers. E-wallets such as DANA have become popular thanks to the ease of digital transactions offered, from online shopping to bill payments. However, this convenience also carries risks, especially related to the use of e-wallets for online gambling among teenagers. Low financial literacy, social influence, promotional incentives, and easy access to e-wallet applications are the main factors that make teenagers vulnerable to gambling practices. This study aims to identify the factors that encourage teenagers to use e-wallets for online gambling and explore preventive measures that can be taken. The results of the study show that the misuse of e-wallets for online gambling transactions can have a significant impact on the mental, social, and financial health of adolescents. Preventive efforts are needed, including financial education, parental supervision, and increased regulation of digital financial applications to protect the younger generation from these risks.